Cathepsin B and D deficiency in the mouse pancreas induces impaired autophagy and chronic pancreatitis - Iwama, Hideaki (Sci Rep, 2021)
The major lysosomal proteases, Cathepsin B (CTSB), Cathepsin D (CTSD) and Cathepsin L (CTSL), are implicated in autophagic activity. To investigate the role of each cathepsin in the exocrine pancreas, we generated mice in which the pancreas was specifically deficient in Ctsb, Ctsd and Ctsl. Each of these gene knockout (KO) and Ctsb;Ctsl and Ctsd;Ctsl double-knockout (DKO) mice were almost normal. However, we found cytoplasmic degeneration in the pancreatic acinar cells of Ctsb;Ctsd DKO mice, similar to autophagy related 5 (Atg5) KO mice. LC3 and p62 (autophagy markers) showed remarkable accumulation and the numbers of autophagosomes and autolysosomes were increased in the pancreatic acinar cells of Ctsb;Ctsd DKO mice. Moreover, these Ctsb;Ctsd DKO mice also developed chronic pancreatitis (CP). Thus, we conclude that both Ctsb and Ctsd deficiency caused impaired autophagy in the pancreatic acinar cells, and induced CP in mice.